2014
DOI: 10.1016/s1470-2045(14)70035-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjuvant exemestane versus anastrozole on bone mineral density for women with early breast cancer (MA.27B): a companion analysis of a randomised controlled trial

Abstract: Summary Background Treatment of breast cancer with aromatase inhibitors is associated with damage to bones. NCIC CTG MA.27 was an open-label, phase 3, randomised controlled trial in which women with breast cancer were assigned to one of two adjuvant oral aromatase inhibitors—exemestane or anastrozole. We postulated that exemestane—a mildly androgenic steroid—might have a less detrimental effect on bone than non-steroidal anastrozole. In this companion study to MA.27, we compared changes in bone mineral densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
1
36
0
2
Order By: Relevance
“…Failure to find any associations in exemestane-treated women in the SNP analysis may have been due to a small sample size being underpowered to detect modest pharmacogenetic effects. Alternatively, non-steroidal versus steroidal AIs have been shown to have different pharmacodynamic effects, and our results may indeed suggest different biological effects (15, 2325). …”
Section: Discussionmentioning
confidence: 69%
“…Failure to find any associations in exemestane-treated women in the SNP analysis may have been due to a small sample size being underpowered to detect modest pharmacogenetic effects. Alternatively, non-steroidal versus steroidal AIs have been shown to have different pharmacodynamic effects, and our results may indeed suggest different biological effects (15, 2325). …”
Section: Discussionmentioning
confidence: 69%
“…The open label Phase III randomized clinical trial MA.27 bone subprotocol (MA.27B), in which exemestane and anastrozole were directly compared, failed to demonstrate a statistically significant difference in spine or hip BMD at 2 years, although there were suggestions that exemestane may have mild bone sparing effects based on differences in rates of osteoporosis diagnosis and new prescription of bisphosphonate medication between the two groups [11, 12]. It is of-note that MA.27B was originally planned for longer follow-up but was truncated when the parent study MA.27 closed [11]. Hence, further exploration of the differential bone effects of steroidal and non-steroidal AI remains clinically relevant [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…However, this finding is not definitive and the rate of fragility fractures was similar in both arms at 4 % [62]. The bone substudy of the comparison study of anastrozole versus exemestane did not demonstrate a statistically significant difference between skeletal outcomes [60].…”
Section: Ai Effects On Bonementioning
confidence: 88%
“…The TEAM trial compared exemestane with tamoxifen and reported a significant decline in BMD at the lumbar spine and hip in the exemestane group [59]. Due to exemestane being a mildly androgenic steroid, it was thought possibly protective on bone compared to other AI's; although, the recent study by Goss et al did not show a difference in BMD when it was compared with anastrozole [60]. In the bone substudy of the phase III trial comparing letrozole to tamoxifen, letrozole was associated with a significant decline in BMD compared to tamoxifen alone [61•].…”
Section: Ai Effects On Bonementioning
confidence: 99%